Association of human resource maintenance and development programs and intention to stay of managers in selected fast food restaurants in Metro Manila - Yuliati, Lilik Noor (1998)
The importance of human resource management in the business world will remain as long as human motivation continues to be a complex, mysterious and yet wonderful phenomenon that baffle and dazzle bosses, administrators, and scholars alike. This study is an attempt to comprehend why and how managers would choose to remain in his or her position, and for how long, given so many internal and external pull and push factors in the workplace and professional environment. It seeks to contribute to enhancing the satisfaction of managers and the corporation, and in the long run, better human resource management. This study assumes that prior to entering and while staying in the fast food company, managers have relatively common environment such as Human Resource(HR) maintenance and development programs. HR maintenance program can come in the form of salary, benefit package, performance appraisal, treatment of supervisor, and work environment, while human resource development programs can be provided through training and career development. The study tested the association between HR maintenance and development programs and the managers' intention to stay and their intended duration of stay in the company given their characteristics such as age, gender educational attainment, work experience, position classification, present tenure, salary rate and work hour.